Human Flea Pulex irritans Linnaeus, 1758 (Insecta: Siphonaptera: Pulicidae) - Chad L. Cross; Estelle Martin; Lucas Brendel (EDIS)
Pulex irritans Linnaeus is commonly known as the human flea owing to its general association with humans, with human dwellings, and with pets and other animals in close association with humans. In fact, this species has been found associated with human archaeological sediments in Europe and Greenland, underscoring the long-term correlation between humans and this flea (Buckland and Sadler 1989). The human flea is cosmopolitan (Mullen and Durden 2019, Gage 2005, Marquardt et al. 2000), but is found in highest abundance in areas where it can readily find mammalian hosts. Though its relative abundance and overall medical importance is disputed, this flea has been implicated as a potentially important vector of the human pathogens causing plague and murine typhus as well as serving as a potential vector of a tapeworm known to parasitize humans (Eldridge and Edman 2004). This review is intended for a general audience interested in understanding the biology, ecology, and medical importance of the human flea.